The effects of job satisfaction and loyalty on intention to stay, in the relationship with pay satisfaction of bankers: A case study of emerging economies - Nguyen, Nam Danh; Uong, Lan Ngoc Thi (Edelweiss Applied Science and Technology, 2025)
The study aimed to evaluate the pay satisfaction of employees working at banks in Hanoi City, Vietnam, a recognized emerging economy in Southeast Asia, and to explore the relationship between pay satisfaction, job satisfaction, loyalty, and the intention to remain within the organization. A total of 406 bankers participated in this research. Insights derived from the structural equation model (SEM) using AMOS 20 software indicated that factors such as pay level, benefits, pay structure, and bonus policy exert a significant influence on job satisfaction. Concurrently, benefits, pay levels, and raises play a critical role in employees’ loyalty. Furthermore, the benefits were found to be statistically insignificant in terms of their intention to remain with the organization. Our findings further demonstrated that job satisfaction and loyalty have a significantly positive impact on employees’ intention to stay with the organization. These findings are beneficial for managers at banks in developing countries, such as Vietnam, in driving intention to stay, improving employee satisfaction, and enhancing employee loyalty. Additionally, limitations and potential directions were deliberated upon.